Coaching and Capacity Building Interventions for One Health Workforce in Southeast Asia: A Scoping Review - Septien Dwi Savandha (Al Makki Health Informatics Journal, 2026)
The One Health approach emphasizes the interconnectedness of human, animal, and ecosystem health, advocating for cross-sector collaboration to combat zoonotic threats. Despite policy advances in Southeast Asia, little is known about coaching and capacity-building efforts for the region's One Health workforce. This review aimed to map such interventions, examine their methods and target groups, assess outcomes, and identify gaps. Using the Arksey and O'Malley framework and PRISMA-ScR reporting, a search across seven databases and gray literature from 2000- 2025 was conducted. Studies included addressed multiple sectors in Southeast Asia and described or evaluated coaching or capacity-building. Two reviewers screened records with a Cohen’s kappa of 0.86. Twenty-nine studies met inclusion criteria; Thailand (27.6%) and Indonesia (24.1%) were most represented. Group training predominated (34.5%), and only one study employed executive coaching. Outcomes clustered at Kirkpatrick Levels 1–2, with 20.7% reaching Level 4. Environmental health professionals and five ASEAN countries remained absent from the evidence base. Coaching efforts remain regionally limited, modality-restricted, and outcomes shallow; gaps include executive coaching, organizational consulting, and environmental health inclusion. Future initiatives should combine personalized coaching with organizational strategies, emphasizing longitudinal research and coverage of ASEAN countries.